Fast T2 mapping using multi‐echo spin‐echo MRI: A linear order approach. Issue 5 (19th May 2020) - Fatemi, Yaghoub; Danyali, Habibollah; Helfroush, Mohammad Sadegh; Amiri, Houshang
Abstract : Purpose: Multi‐echo spin‐echo sequence is commonly used for T 2 mapping. The estimated values using conventional exponential fit, however, are hampered by stimulated and indirect echoes leading to overestimation of T 2 . Here, we present fast analysis of multi‐echo spin‐echo (FAMESE) as a novel approach to decrease the complexity of the search space, which leads to accelerated measurement of T 2 . Methods: We developed FAMESE based on mathematical analysis of the Bloch equations in which the search space dimension decreased to only one. Then, we tested it in both phantom and human brain. Bland‐Altman plot was used to assess the agreement between the estimated T 2 values from FAMESE and the ones estimated from single‐echo spin‐echo sequence. The reliability of FAMESE was assessed by intraclass correlation coefficients. In addition, we investigated the noise stability of the method in synthetic and experimental data. Results: In both phantom and healthy participants, FAMESE provided accelerated and SNR‐resistant T 2 maps. The FAMESE had a very good agreement with the single‐echo spin echo for the whole range of T 2 values. The intraclass correlation coefficient values for FAMESE were excellent (ie, 0.9998 and 0.9860 < intraclass correlation coefficient < 0.9942 for the phantom and humans, respectively). Conclusion: Our developed method FAMESE could be considered as a candidate for rapid T 2 mapping with a clinically feasible scan time.